Enrolment, achievement and retention on 'traditional' and 'Use of Mathematics' pre-university courses - Hutcheson, Graeme D.; Pampaka, Maria; Williams, Julian (Research in mathematics education, 2011)
This paper investigates enrolment, attainment and drop-out rates for two different English pre-university advanced mathematics, AS-level, courses, a 'traditional' and an innovative 'Use of Mathematics' pre-university course. Very different student profiles were found for those enrolled on each course, and a model of attainment at the pre-university level showed a relatively complex relationship with prior achievement at the end of compulsory schooling. Although those pupils who had relatively high prior achievement tended also to achieve relatively highly on the pre-university courses, this relationship was not evident for lower scores. Those pupils with 'mid-range' prior attainment tended to make the smallest gains. Taking prior attainment into account, the difference in attainment outcomes between the two courses is small. However, these courses do differ with respect to the number of students retained, with the 'Use of Mathematics' course retaining a significantly higher proportion of the students. Contextual factors are discussed, suggesting implications for policy and practice in mathematics education.